1996
DOI: 10.1093/humupd/2.4.323
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasonography in the evaluation of endometrial receptivity following assisted reproductive treatments: a critical review

Abstract: We set out to estimate the value of ultrasonographic parameters as prognostic indicators of implantation following in-vitro fertilization (IVF) and embryo transfer. Our survey included 414 natural cycles, 3558 cycles following ovarian stimulation for IVF and embryo transfer, and 411 cycles with hormone replacement therapy for oocyte donation, reviewing 27 reports identified in a computerized literature research. The ultrasonographic prognostic indicators for implantation evaluated included peri-ovulatory endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
168
1
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(188 citation statements)
references
References 59 publications
11
168
1
8
Order By: Relevance
“…At the same time, it is in accordance with the observed detrimental effect of smoking on endometrial receptivity [6,25]. It is noteworthy that in both our groups, endometrial thickness was above the suggested lower limit, which may explain this negative effect [26].…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, it is in accordance with the observed detrimental effect of smoking on endometrial receptivity [6,25]. It is noteworthy that in both our groups, endometrial thickness was above the suggested lower limit, which may explain this negative effect [26].…”
Section: Discussionsupporting
confidence: 91%
“…The pregnancy rate was low despite the adequate number of embryos that were transferred. The thinnest endometrium which was associated with a successful pregnancy was 6.8 mm thick, quite close to the established cutoff and in conformity to published data [17]. The outcome of these 11 pregnancies (eight miscarriages, two late terminations due to malformations and one live birth) demonstrated that these patients had a poor reproductive prognosis even if some endometrial thickening or implantation did occur.…”
Section: Discussionsupporting
confidence: 87%
“…In a third category of studies the endometrial thickness was related to the IVF outcome, but only in correlation with other parameters [15,16]. Different thresholds of endometrial thickness were suggested as essential for successful implantation and most demonstrated that no pregnancy was established when the thickness of the pre-ovulatory endometrium was <6 mm [17]. Nevertheless, Sundstrom [18] have reported a successful outcome of an IVF cycle in a patient with an endometrial thickness of no more than 4 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been developed to evaluate endometrial receptivity, such as ultrasound examination of the endometrium [33,34], the histological dating of an endometrial biopsy [35], endometrial cytokines in uterine flushing [36] and the genomic study of a timed endometrial biopsy [37].…”
Section: Effects Of Excessive Ovarian Response On Endometrial Receptimentioning
confidence: 99%